ChemInform Abstract: Synthesis and Reactivity Profile of Ylidenemalononitrile Enamines and Their Ester Analogues Towards Electrophiles and Nucleophiles. Issue 2 (23rd December 2015) - Longstreet, Ashley R.; Rivalti, Daniel; McQuade, D. Tyler
Abstract: A wide range of the title enamines are synthesized from ylidenemalononitriles and ylidenecyanoacetates.